Understanding the level of halal awareness among Muslim and non-Muslim young consumers in Malaysia - Mat Isa, Mohamad Parhan; Mohamed Ismail, Risyawati (2015)
With the rising of health concern, especially in the food industry, the halal practices can be referred as a guide to better and safer food consumption s. The objective of this study relates to the level of halal awareness of Muslim and non-Muslim youth and how its connections to the practices and rules of halal in Malaysia.This study also aimed to discover how well Malaysian youth understands the halal concepts and practices.Data expected to be collected through the questionnaires involving Muslim and Non-Muslim youth of Malaysia especially students of Universiti Utara Malaysia.This study use quantitative methods to analysis and determine the level of understanding of Muslim and Non-Muslim youth related to the halal concept and practices. The data from survey analysed using the Statistical Package for the Social Science (SPSS).The statistical results from this study aims to explain the behavior of Malaysian youth in regards to their consumerism on halal products. The finding from this study will also provide support for future research that aim to explain a larger portion of halal consumerism, a topic which is still in its infancy in Malaysia.